Brand Mergers: Examining Consumer Responses to Name and Logo Design - Machado, J. C. (2014)
It is critical to investigate reactions to the various name and logo redeployment alternatives available in the context of a merger. Yet research on this topic is relatively limited. This study contributes to the literature, by developing a typology of the visual identity structures that may be assumed in the context of a merger, as well as an exploratory study (n = 467) analysing consumers’ preferences regarding the alternative branding strategies. Results suggest that there is a clear preference for figurative logos, and also that the logo may play a role as important as the name, ensuring a connection to the brand’s past. Data also show that the choice of the logo reflects consumers’ aesthetic responses, whereas the choice of the name reflects consumers’ evaluation of the brand’s offer or off the brand’s presence in the market. These results should guide managers in the evaluation and choice of the post-merger branding strategy.